Ocean warming and acidification affect the transitional C:N:P ratio and macromolecular accumulation in the harmful raphidophyte Heterosigma akashiwo - Satheeswaran Thangaraj; Jun Sun (Communications Biology, 2023)
Physiological experiments in Heterosigma akashiwo provide metabolic insights to the future of algal blooms under warming and acidifying ocean conditions.